Comparison of Concentration Difference between ST2 and NT-Pro BNP Before and After Ace-Inhibitors in NYHA III-IV Hearts Failure Patients - Veronika Juanita Maskito; Leonita Anniwati; Aminuddin Aminuddin (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
The American Heart Association (2016) stated that at the age of forty the risk of developing heart failure is one in five. Medication is based on clinical signs and symptoms that are often late. Early cardiac markers are required to guide therapy. This study compared the difference between ST2 and NT-ProBNP concentrations before and after ACE inhibitors (ACE-I) in NYHA III-IV heart failure patients. This was a randomized prospective observational study without controls. The respondents were males or females, 21-75 y.o in NYHA III-IV heart failure patients. Twenty-five respondents were appropriate to inclusion criteria. The ST2 was measured by Quantikine®ST2/IL-33R quantitative sandwich ELISA immunoassay while NT-proBNP was measured by Immulite Turbo® 1000. Majority of respondents were males (60%) and had comorbidities(60,7%), consisting of NYHA Class III(36%) and IV(64%). Coronary artery disease and valvular heart disease (40%,36% respectively). Length of stay was 6.4±3.4days. The concentration difference of ST2 and NT-proBNP before and after ACE-I were both significant, however, NT-proBNP was more significant (p=0,001 vs p=0,023). NYHA at admission influenced ST2 difference but not NT-proBNP. NT-proBNP concentration correlated to length of stay while ST2 was not. ST2 had negative correlation with age, no correlation to GFR and weight. NT-proBNP was correlated to weight, negatively correlated to GFR, not correlated to age. ACE-I subtypes difference did not affect the study result. NT-proBNP was a better heart failure cardiac marker than ST2 due to its ability in diagnosis, prognosis and showing more significant difference after ACE-I administration.